PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA LOYALITAS KONSUMEN STUDI KASUS GERAI DONUTS DI TANGERANG - Herman Nurtjahjo; Rianto Nurcahyo; Marcel Marcel; Rajkawel Rajkawel (Universitas Pandanaran, 2018)
Consumer Loyalty is an important thing to have in tight business competition. The purpose of this study is to find out how brand image, service quality, and store atmosphere may influence customer satisfaction and its impact on customer loyalty on Donuts XYZ products. This research uses path analysis techniques and uses quantitative research methods with data collection techniques using questionnaires where the analysis unit is the consumer who domiciled in Kotamadya Tangerang. The result of this research is brand image, service quality, and store atmosphere have influence customer loyalty through customer satisfaction, with the greatest influence owned by the outlet atmosphere of 24.4% Keywords: brand image, service quality, store atmosphere, customer satisfaction, customer loyalty.